FACTORS WATER CHARACTERISTIC AS PREDICTING DIARRHEA UNDER 5 YEARS - Nugroho Susanto (Poltekkes Kemenkes Semarang, 2021)
Risk Factors diarrhea deaths associated to unsafe water and inadequate sanitation. Water supply is very important to decrease of diarrhea disease. Living around canal is a one of risk diarrhea incident. Improved water sanitation, water facilities, and hygiene water decrease of diarrhea disease. Study aims to know dominant factor related water sanitation which is more appropriate than diarrhea in volcano area disaster. Study design used cross sectional community-based survey. Population and sample size were required 1142 household. Data collected such as sufficient of water source, water colored, smelly water, taste water, water cooked, distance of absorption. Data were analyzed performed using SPSS. Data analysis performed a descriptive analysis, statistic test with chi square and logistic regression with confidence interval 95%. Study that sufficient of water 97.2%, no water colored 98.4%, no smelly water (95.3%), no taste water 95.4%, water cooked 98.2%, distance of absorption more than 11 meter 78%. Risk factor for diarrhea such as taste water OR = 7.3 (3.7-14.4), smelly water OR = 6.9 (3.5-13.6) and distance of absorption OR = 3.4 (2.0-5.7). Factor highest contribution for diarrhea is distance absorption (Exp β = 1.70 CI; 1.701-4.906). Distance absorption less than 11 meters is main factor contributing for diarrhea. Factor dominant contribution for diarrhea is distance of absorption less than 11 meter.